Theoretical study of the II-VI solar cells semiconductor material arrangements effect using the one-dimensional Schrodinger equation - Tamara Pingki; Dafik Dafik; Bambang Supriadi (Universitas Sebelas Maret, 2024)
Solar cells are electronic devices that function to convert light energy from sun into electrical energy. Solar cells can work well if the materials used are also right so they can absorb light energy to the maximum. The solar cell materials used in this study are II-VI semiconductors, there are CdS (P), CdSe (Q), and CdTe (R). The purpose of this study was to find the combination of materials has the largest transmission coefficient which was analyzed using the Schrodinger equation (analytic) and Matlab R2022a (numeric). The greater the transmission coefficient, the greater the light energy absorbed by the solar cells, so that the generated electrical energy is also greater. The materials are arranged into 3 uniform arrangements and 6 combined arrangements with a maximum electron energy of 1 eV. The results showed that the largest transmission coefficient in the CdS array was 0.9925 at 1.0000 eV, the largest transmission coefficient in the CdSe array was 1.0000 at 0.8140 eV, and the largest transmission coefficient in the CdTe array was 1.0000 at 0.7330 eV. Meanwhile, in the combined arrangement, the biggest transmission value is 0.9823 at 0.9570 eV in the QPR and RPQ arrangements.